Characteristics of Orthopedic Treatment of Diabetic Patients - Chaqqonov Faxriddin Xusanovich; Aliyev S.; Eshqobilov Q; Majidov B.; Ebdullayev M. (Academia One, 2023)
Diabetes mellitus is the most important medical and social problem of modern society. Currently, according to the International Diabetes Federation (IDF), there are 415 million diabetics worldwide. [1] According to WHO, the term "diabetes mellitus" refers to a metabolic disorder of multiple etiologies characterized by chronic hyperglycemia with abnormal carbohydrate, fat, and protein metabolism as a result of impaired insulin secretion and/or impaired insulin action. In this regard, primary diabetes mellitus has two forms: type I - insulin-dependent diabetes mellitus, characterized by inadequate insulin synthesis by Langerhans cells; type II - non-insulin-dependent diabetes mellitus, which is associated with chronic hyperglycemia and results from a violation of the interaction between insulin and tissue cells It develops as a result of a violation of the interaction between insulin and tissue cells (WHO, 1999). [Secondary or symptomatic diabetes mellitus is also distinguished, which is caused by diseases or substances affecting the endocrine organs of the pancreas or the insulin receptors
Keywords: diabetes; orthopedic treatment; oral cavity; midline washing